Inclusive Education and Quality Strategies in Achieving Educational Equality in Indonesia - Sholihah, Binti Mar’atus (Academia Publication, 2024)
Inclusive education is a crucial approach to creating equality for all students, including those with special needs. Educators play a key role in implementing inclusive education, ensuring that every student has fair access to quality learning. This study aimed to identify effective strategies that educators could use to promote inclusive education and address various challenges in the process. A qualitative study approach was applied, utilizing data collection methods such as in-depth interviews and literature analysis. The findings revealed that strategies such as differentiated instruction, the use of assistive technology, and professional training and development for educators were highly effective in supporting the implementation of inclusive education. Furthermore, this study highlighted the importance of institutional support and collaboration between educators, parents, and the community in achieving educational equity. In conclusion, inclusive education not only enhanced student engagement and achievement but also fostered a more inclusive and responsive learning environment for all learners.